Предмет: Математика,
автор: mazurdima703
5 - 3(2 - 0,4 x) = 0,4(4x + 1)
Помогите
Ответы
Автор ответа:
1
5,6-3*(2-0,4x)=0,4*(4x+1)
5,6-6+1,2х=1,6х+0,4
-0,4-0,4=1,6х-1,2х
0,4х=-0,8
х=-0,8:0,4
х=-2
5,6-3*(2-0,4*(-2))=0,4*(4*(-2)+1)
-2,8=-2,8
5,6-6+1,2х=1,6х+0,4
-0,4-0,4=1,6х-1,2х
0,4х=-0,8
х=-0,8:0,4
х=-2
5,6-3*(2-0,4*(-2))=0,4*(4*(-2)+1)
-2,8=-2,8
mazurdima703:
это вообще другое уравнение
Похожие вопросы
Предмет: Окружающий мир,
автор: halia34
Предмет: Русский язык,
автор: Дария200з
Предмет: Русский язык,
автор: alina445682685
Предмет: История,
автор: dima8910673
Предмет: Английский язык,
автор: maksit007